Comparison of Two Ventilation Control Strategies in the First Passive House Standard Norwegian School. Issue 4 (1st March 2016) - Cablé, Axel; Hammer, Hugo Lewi; Mysen, Mads
Abstract: The perceived indoor climate resulting from two ventilation control strategies was evaluated in a classroom of the first school built according to the Norwegian passive house standard. Both strategies consisted of varying the ventilation rate according to room demand, ie. Demand-Controlled Ventilation (DCV). The existing strategy consisted of varying the ventilation rate in order to maintain a constant carbon dioxide concentration of 800 ppm in the classroom (constant-CO2 control). A new strategy was implemented which consisted of a combined CO2 and temperature control, ie. to control towards a proportionally lower CO2 concentration when the indoor temperature increases. The aim with this strategy was both to address overheating and the fact that perceived indoor air quality decreases when temperature rises. Indoor climate measurements, as well as questionnaires on the perceived indoor air quality and thermal comfort (completed by the pupils), were used to compare both strategies. An acceptable perceived indoor climate was reported for both strategies, with a slight improvement for the combined CO2 and temperature control. The data from the questionnaires were then analyzed using a random effect linear regression model. The regression analysis revealed that the combined CO2 and temperature control reduced the discomfort by variations of the indoor temperature significantly compared to the existing strategy (constant-CO2 control). If correctly implemented, combined CO2 and temperature DCV therefore appears to be a relevant solution for schools built to passive house standard.